Keperawatan kritis demystified /Chintyas Lee Terry, aurora weaver; penerjemah eri Yanuar Akhmad,, Happy Indah Kusumawati; editor aAldo Sahala - TERRY, Cynthia Lee; Aurora Weaver; Weaver, Aurora; Eri Yanuar Akmad; Happy Indah Kusumawati; Aldo Sahala (Rapha Publishing, 2013)
viii, 554 hlm :ilus.; 23 cm